PENGARUH APLIKASI WORDWALL TERHADAP KEMAMPUAN BERHITUNG ANAK DI TAMAN KANAK-KANAK NEGERI PEMBINA 01 LINGGO SARI BAGANTI - Aulia, Tazkia; Vivi Anggraini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early numeracy is one of the fundamental skills that should be developed during early childhood, as it provides the foundation for learning mathematics at higher levels of education. However, the numeracy skills of children at TK Negeri Pembina 01 Linggo Sari Baganti were not yet optimally developed, indicating the need for more engaging and interactive learning media. This study aimed to examine the effect of the Wordwall application on the numeracy skills of children aged 5–6 years. This study employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The population consisted of all Group B children, while the sample included 28 children selected through purposive sampling and divided equally into an experimental group and a control group. Data were collected through observation using an instrument that assessed number recognition, number sequencing, and simple arithmetic operations. The data were analyzed using normality, homogeneity, and Independent Samples t-tests with IBM SPSS Statistics version 19. The results showed that the experimental group's mean score increased from 7.14 on the pretest to 18.57 on the posttest, whereas the control group's mean score increased from 6.93 to 13.57. The hypothesis test indicated a significance value of p < 0.05, demonstrating a significant difference between the two groups. Therefore, the Wordwall application had a significant positive effect on the numeracy skills of children aged 5–6 years and can serve as an effective digital learning medium for early childhood mathematics instruction.